Physical activity practice´s characteristics of students of Faculty of Education (University of Seville) - Carolina Castañeda Vázquez; Santiago Romero Granados; Francis Ríes (Federación Extremeña de Balonmano; University of Extremadura, 2012)
The aim of this research is to know about students´ physical activity from Faculty of Education of University of Seville, and its characteristics. The sample (N=409) is constituted for students from the different degrees of this Faculty (±4.8%; 95%CI). A specific questionnaire, built to that effect, was used to obtain dates. This instrument was validated by different experts on this area of studies, and statistic tests was done to check its reliability (Alpha Cronbach: .78) using SPSS V.15. The main results showed that 62.19% of students do physical activity regularly. Students prefer recreational activities or exercise aimed at being fit or watching health instead competitive games. Activities done by students inside University are very similar to activities done out of this. They also do exercise during all academic year, preferably along the all week or from Monday to Friday, and especially in the afternoon. This group usually practice with friends, classmates or workmates, but lonely too, and they prefer public areas and public or private sport facilities for their sport practice. Key Words: University students, physical activity practice, leisure time.